THE LEGAL AND ETHICAL OBLIGATIONS OF SCHOOL SOCIAL WORKERS - Reyneke, Roelf (Social Work/Maatskaplike Werk, 2020)
In recent years social workers have been appointed in some schools on the assumption that social work services can contribute towards improving education in schools by supporting the psychosocial development of learners. Social workers not only place a high priority on ethical conduct, but as custodians of the Children’s Act, they also have distinct legal obligations towards children. However, social work ethics and these legal obligations could create ethical dilemmas. This narrative review article provides the background to school social work and explains some of the legal and ethical obligations that social workers face in this environment. A few common ethical dilemmas are also discussed.